2013
DOI: 10.1037/a0031522
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and cognitive social processes are impaired in Parkinson's disease and are related to behavioral disorders.

Abstract: Emotional and cognitive social processes were found to be impaired in Parkinson's disease. This impairment may account for the emergence of social behavioral disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 71 publications
(112 reference statements)
6
59
1
1
Order By: Relevance
“…They reported a deficit in patients whatever the treatment condition, but found a greater one among unmedicated patients. This is consistent with the positive correlation between patients' performance and daily levodopa‐equivalent dose (LED) found by Assogna et al45 However, no other authors who looked for such correlations found this result 19, 28, 38, 45, 64, 65, 67, 75. Otherwise, several studies have reported a beneficial effect of DRT on FER in PD.…”
Section: Discrepancies In Resultssupporting
confidence: 84%
“…They reported a deficit in patients whatever the treatment condition, but found a greater one among unmedicated patients. This is consistent with the positive correlation between patients' performance and daily levodopa‐equivalent dose (LED) found by Assogna et al45 However, no other authors who looked for such correlations found this result 19, 28, 38, 45, 64, 65, 67, 75. Otherwise, several studies have reported a beneficial effect of DRT on FER in PD.…”
Section: Discrepancies In Resultssupporting
confidence: 84%
“…Many have questioned whether persons with PD are also impaired their ability to perceive facial expressions of emotion. The findings from individual studies have been mixed; some studies have reported impaired perception of facial expressions of emotion in PD [5][6][7]9,10,[12][13][14][15][16]22,32,34,35,38,44,47,50,51,58,59,68] whereas others have found no such impairment [2,18,20,31,45,53,60,63,65]. Despite mixed findings from individual studies, a recent meta-analysis by Gray and TickleDegnen [30] concluded that those with PD were impaired in perceiving facial expressions of emotion and that this impairment was unrelated to the ability to perceive visual form.…”
Section: Introductionmentioning
confidence: 92%
“…Perceiving the mental and emotional states of other individuals is an inevitable requirement of social relationships. In the recent years, researchers have turned their attention to the topic of social relations in IPD and begun to question to what extent would such deficits affect social functioning in IPD (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…The motor symptoms in IPD are well known and the treatments have focused primarily on this area. However, other less emphasized non-motor symptoms affect cognitive capabilities including personality and mood, social functions and quality of life (4,5).…”
Section: Introductionmentioning
confidence: 99%